Synchronized Phasor Measurements and Their Applications - Phadke, A.G. (Springer, 2017)
Synchronized Phasor Measurement and Their Applications presents the historical development of the synchronized phasor measurement technology, which is the most accurate wide area measurements (WAMS) technology for power systems, and points the path for the applications of these measurements to be realized in coming years. The synchronized phasor measurement concept was introduced by the authors about 25 years ago and has been developing at a steady pace through the research of the authors as well as their colleagues throughout the world. It is now a mature technology with products being offered by leading manufacturers of electric power equipment.